Detection and Characterization of 1, 2‐Dibromoethane‐Derived DNA Crosslinks Formed with O6‐Alkylguanine‐DNA Alkyltransferase1. Issue 49 (15th October 2013) - Chowdhury, Goutam; Cho, Sung‐Hee; Pegg, Anthony E.; Guengerich, F. Peter
<x xml:space="preserve">Abstract</x> A combination of chemical modifications and LC‐tandem MS was used for the structure elucidation of various ethylene crosslinks of DNA with O6‐alkylguanine‐DNA alkyltransferase (AGT, see picture). The elucidation of the chemical structures of such DNA–protein crosslinks is necessary to understand mechanisms of mutagenesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>